Analisis Sedimentologi Dan Fasies Pengendapan Formasi Kerek Di Daerah Biren Dan Kerek, Kabupaten Ngawi Jawa Timur - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
On the Bengawan Solo River hank, Biren and Kerek Areas, Ngawi-East Java province, there are exposed good, fresh and complete sequence outcrops / stratigraphy of Kendeng Zone. These outcrops show some .formations. i.e. Kerek, Kalibeng. Klitik, Pncangan and Kabuh Formations. This study is only focused on Kerek Formation, including Banyuurip and Sentul Members. The goal of the study is to analyze sedimentology and depositional fiicies of the Kerek Formation by measured section (MS) method. The result of the 250 m measured section shows that the lithology of this sequence was dominated by intercalation of sandstone and claystone, vary in thickness and as products of turbidity series. Banyuurip Member comprises of calcareous sandstone facies (F-8) and intercalation calcareous sandstone and claystone (F-9). Sedimentary structure, was observed, which is dominated by parallel lamination and convolute lamination. Sentul Member comprises of calcareous sandstone (F-8) and intercalation calcareous sandstone and claystone (F-9a and F-9b), in some parts intercalated by conglomeratic sandstone from F-5. Both Banyuurip and Senud Members were deposited in the middle â outer fan environment and have Middle â Upper Miocene (N13 â N17) age. The main flow of the deposits was formed by sandy high density to low density turbidity current (SHDTC â LDTC). The vertical facies change of the Banyuurip to Sentul Member is characterized by transgressive phase and followed by ratio change of sandstone and claystone components. To the upper part, claystone component in the Sentul Member is more dominant than sandstone fractions.